2021
DOI: 10.1097/md.0000000000024603
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine reduces contrast-induced nephropathy in patients with renal insufficiency undergoing coronary angiography and angioplasty

Abstract: Objectives: This systematic review and meta-analysis assesses the utility of trimetazidine (TMZ) to prevent contrast induced nephropathy (CIN) in patients with renal insufficiency undergoing coronary angiography and angioplasty. Materials and methods: This meta-analysis was formulated and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search of databases was conducted by 2 researchers independently for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Our results provide robust evidence adding to the previous systematic review and meta-analysis by Behzadi et al focusing on patients with renal insufficiency [2]. In contrast to this previous meta-analysis [2] that included a total of 1611 patients from 11 articles, our present analysis included robust data from 2158 patients from 9 articles published in the English language only within the last 15 years.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our results provide robust evidence adding to the previous systematic review and meta-analysis by Behzadi et al focusing on patients with renal insufficiency [2]. In contrast to this previous meta-analysis [2] that included a total of 1611 patients from 11 articles, our present analysis included robust data from 2158 patients from 9 articles published in the English language only within the last 15 years.…”
Section: Discussionsupporting
confidence: 74%
“…CIN may affect 1.6% to 2.3% of those undergoing diagnostic interventions but is known to affect up to half of the high-risk patients undergoing coronary intervention [2]. It is an important cause of hospital-acquired kidney injury, especially in those with risk factors such as hypertension, diabetes mellitus, previous myocardial infarction, higher age, damaged left anterior descending artery, Killip class of 2 or higher, lower left ventricular ejection fraction (LVEF), reduced glomerular filtration rate, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More research is needed to show the impact of N-acetylcysteine in reducing AKI [87]. Therapeutic interventions that have been shown to decrease CIAKI, in the catheterization lab setting, include hydration, the RenalGuard system [76], and trimetazidine [88], a fatty acid oxidation inhibitor with cardioprotective effects.…”
Section: Contrast-induced Acute Kidney Injurymentioning
confidence: 99%
“…However, the side effects caused by contrast agent during percutaneous coronary intervention cannot be ignored, especially the occurrence of contrast-induced nephropathy (CIN) , which significantly affects the prognosis of patients [1] . Studies have confirmed [1][2][3] that the incidence of CIN in the general population is 5.8%, but it is higher than 50% in some high-risk groups, which must be taken seriously by relevant personnel. However, the exact mechanism of CIN occurrence is still unknown, and it is generally accepted that it may have certain relationship with the renal medullary ischemia and hypoxia, renal damage caused by oxygen free radical, toxic effect of contrast agent and inflammatory reaction [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%